2017
DOI: 10.18203/issn.2454-5929.ijohns20174336
|View full text |Cite
|
Sign up to set email alerts
|

Versatility of the submental island flap in head and reconstruction

Abstract: <p class="abstract"><strong>Background:</strong> Head neck cancer is major cause of morbidity and mortality worldwide. India has one of the highest incidences of oral cancer and accounts for about 30% of all new cases annually. Ablative surgery is main stay of treatment which is followed by reconstructive surgery. Microvascular surgery revolutionized onco-reconstruction which requires great expertise even in tertiary cancer centre and it is not possible many times due to long waiting list for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Post-operative adjuvant RT negates this problem to some extent. Katre et al [10] reported their previous experience with submental flap, in which they experienced similar issue of hair-bearing skin in oral cavity in males, who did not receive adjuvant RT. These patients then had to undergo a second procedure of skin de-epithelialization or laser epilation at a later stage which further adds to the cost incurred by the patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Post-operative adjuvant RT negates this problem to some extent. Katre et al [10] reported their previous experience with submental flap, in which they experienced similar issue of hair-bearing skin in oral cavity in males, who did not receive adjuvant RT. These patients then had to undergo a second procedure of skin de-epithelialization or laser epilation at a later stage which further adds to the cost incurred by the patients.…”
Section: Discussionmentioning
confidence: 99%
“…The submental flap has a long and reliable vascular pedicle, which provides a pedicle length up to 8 cm, with an average of 2-mm arterial diameter. Although the largest skin paddle used was 14 × 7 cm according to the English literature, it has been proposed that a skin paddle up to 18 × 7 cm is possible, depending on the laxity of the submental skin [10].…”
Section: Discussionmentioning
confidence: 99%